Geopolitical Consequences of the COVID - 19 Pandemic - Raščan, Stanislav (Anali PAZU HD, 2022)
As news and reports spread of the new virus from Wuhan at the end of 2019, many compared it to the Severe Acute Respiratory Syndrome (SARS) outbreaks from 2002 to 2004. Instead of the SARS outbreak, we could compare COVID-19 to the Spanish flu. Similarly, to the Spanish flu, the COVID-19 pandemic did not single out a nation, infecting many and claiming millions of lives. The key economic issue with the COVID-19 pandemic is whether this is simply a bad recession or a wave of economic depression.